A High-Resolution Hydrodynamic Investigation of Brown Trout (Salmo trutta) and Rainbow Trout (Oncorhynchus mykiss) Redds - Marchildon, Mason (University of Waterloo, 2009)
High-resolution velocity measurements were undertaken over a series of redds and riffles on a gravel-bed stream to quantify the hydrodynamics preferred by spawning brown trout (Salmo trutta) and rainbow trout (Oncorhynchus mykiss) for redd-site selection. On each riffle studied, over 6,000 velocity measurements per day were acquired to quantify the velocity, depth, Reynolds number, Froude number, bed shear, and turbulent kinetic energy per unit area of streambed in attempts to relate fluid properties to redd-site selection, relative to remaining riffle structures. Results showed that velocity, Reynolds number, and Froude number vary widely at the redd- and riffle-scale with no apparent correlation to spawning location preference. Turbulent kinetic energy per unit area consistently demonstrated a strong correlation with redd locations whereby the metric maintained low values (i.e., unidirectional flow with little turbulence) where redds and attempted redds were observed. Habitat suitability indices were applied at the reach-, riffle-, and redd-scale using the results of the high-resolution velocity measurements. Findings demonstrated that habitat suitability indices, which are based on reach-scale hydraulics, were adequately represented at the reach scale. However, by decreasing the scale to the riffle- or redd-scale, where increasing heterogeneity in the flow regime is revealed, habitat suitability indices failed to adequately reflect the habitat conditions preferred by the spawning fish.
Keywords: Redds; Brown trout; Rainbow trout; Spawning; Whiteman's creek; Geomorphology; Physical Habitat; Pulse Coherent Acoustic Doppler Profiler; Lotic Ecology; Civil Engineering